Rapamycin/metformin co‐treatment normalizes insulin sensitivity and reduces complications of metabolic syndrome in type 2 diabetic mice. Issue 9 (19th August 2022) - Reifsnyder, Peter C.; Flurkey, Kevin; Doty, Rosalinda; Calcutt, Nigel A.; Koza, Robert A.; Harrison, David E.
Abstract: Rapamycin treatment has positive and negative effects on progression of type 2 diabetes (T2D) in a recombinant inbred polygenic mouse model, male NONcNZO10/LtJ (NcZ10). Here, we show that combination treatment with metformin ameliorates negative effects of rapamycin while maintaining its benefits. From 12 to 30 weeks of age, NcZ10 males were fed a control diet or diets supplemented with rapamycin, metformin, or a combination of both. Rapamycin alone reduced weight gain, adiposity, HOMA‐IR, and inflammation, and prevented hyperinsulinemia and pre‐steatotic hepatic lipidosis, but exacerbated hyperglycemia, hypertriglyceridemia, and pancreatic islet degranulation. Metformin alone reduced hyperinsulinemia and circulating c‐reactive protein, but exacerbated nephropathy. Combination treatment retained the benefits of both while preventing many of the deleterious effects. Importantly, the combination treatment reversed effects of rapamycin on markers of hepatic insulin resistance and normalized systemic insulin sensitivity in this inherently insulin‐resistant model. In adipose tissue, rapamycin attenuated the expression of genes associated with adipose tissue expansion ( Mest, Gpam ), inflammation ( Itgam, Itgax, Hmox1, Lbp ), and cell senescence ( Serpine1 ). In liver, the addition of metformin counteracted rapamycin‐induced alterations of G6pc, Ppara, and Ldlr expressions that promote hyperglycemia and hypertriglyceridemia. Both rapamycin and metformin treatment reduced hepatic Fasn expression, potentially preventing lipidosis. These results delineate a state of "insulin signaling restriction" that withdraws endocrine support for further adipogenesis, progression of the metabolic syndrome, and the development of its comorbidities. Our results are relevant for the treatment of T2D, the optimization of current rapamycin‐based treatments for posttransplant rejection and various cancers, and for the development of treatments for healthy aging. Abstract : Rapamycin and metformin combination treatment in a mouse model of type 2 diabetes, NONcNZO10/LtJ males, prevents hyperinsulinemia, normalizes insulin sensitivity, and reduces pathological complications of diabetes. When combined, each compound prevents the negative side effects of the other. These results are relevant for the treatment of diabetes, the optimization of current rapamycin‐based treatments, and the development of treatments for healthy aging.